2002
DOI: 10.1084/jem.20011971
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of Cytochrome c Presentation by IEk

Abstract: The COOH-terminal peptides of pigeon and moth cytochrome c, bound to mouse IEk, are two of the most thoroughly studied T cell antigens. We have solved the crystal structures of the moth peptide and a weak agonist–antagonist variant of the pigeon peptide bound to IEk. The moth peptide and all other peptides whose structures have been solved bound to IEk, have a lysine filling the p9 pocket of IEk. However, the pigeon peptide has an alanine at p9 shifting the lysine to p10. Rather than kinking to place the lysin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
38
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 63 publications
1
38
0
Order By: Relevance
“…For example, peptide studies predicted the properties of the p1, p6, and p9 pockets of IE k (44)(45)(46). The structure of IE k with bound peptides confirmed these conclusions and determined the properties of the p4 pocket (12,23).…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…For example, peptide studies predicted the properties of the p1, p6, and p9 pockets of IE k (44)(45)(46). The structure of IE k with bound peptides confirmed these conclusions and determined the properties of the p4 pocket (12,23).…”
Section: Resultssupporting
confidence: 59%
“…In nearly all MHCII structures the p7 amino acid points laterally toward the ␤-chain ␣-helix. In some cases, its contribution to MHC interaction is minimal because of a small side chain (12)(13)(14)23) or a rotamer that brings the side chain to the surface (12,16,20,21). In a few cases, the p7 rotamer buries a portion of the side chain with considerable ␤-chain interaction (11,15,17,18).…”
Section: Resultsmentioning
confidence: 99%
“…Although the loss of recognition of nMCC 88 -103 by the T cell hybridoma 2B4 constituted a negative result, this observation provided the first clear evidence that modification of tyrosine to nitrotyrosine could have an impact on the process of T cell recognition. Previous studies have indicated that Y97 of MCC 88 -103 is not involved in MHC binding (29); however, we wanted to eliminate the possibility that conversion of Y97 to (27,29). Furthermore, these results demonstrate unequivocally that conversion of tyrosine to nitrotyrosine has potentially profound consequences in terms of T cell recognition.…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose we have used the well-established IE k -restricted peptide from the model Ag moth/pigeon cytochrome c (MCC 88 -103 ). The MCC 88 -103 peptide comprises one of the most extensively studied model systems for understanding MHC restriction and T cell recognition and continues to be widely used as a tool for understanding the processes of T cell tolerance and T cell activation (27,28). The IE k -restricted MCC 88 -103 peptide contains a single tyrosine residue (Y97) that is not involved in MHC binding, but is critically important for T cell recognition (27,29).…”
mentioning
confidence: 99%
See 1 more Smart Citation